PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTER UNTUK SISWA KELAS X SMK SEMESTER GANJIL PADA MATA PELAJARAN INSTALASI LISTRIK DASAR - Dendy Dewa Widjaya Putra; Syaad Patmanthara (SENTIA 2016, 2016)
Learning activities problems occur at SMK PGRI 3 Malang are less-interested students in Basic Electricity Installation, caused the teacher in the learning process is still using textbooks and media powerpint  form.  From  these  problems,  the  researcher  develop  computer  assisted  learning  media  of  Basic Electrical Installation Subject. The results of this product is CD (Compact Disk) form. The purpose of this product is: (1) To create computer assisted learning media of basic electricity installation subject for SMK; (2) Developing computer assisted learning media of basic electricity installation subject for SMK; (3) Testing the computer assisted learning media properness of basic electricity installation subject for SMK. The research model used in development is a Borg & Gall model. Validation is validated by some experts, that are: (1) The product validated by expert media reached 91.25%; (2) Material expert reached 89.70% (3) Testing results by the  teachers  reached  98.53%;(4)  Testing  results  by  student  reached  92.50%.  Based  on  the  results  of  the validation, it can be concluded that the Computer Assisted Learning Media of Basic Electricity Installation Subject is properly to be used in the learning activities at SMK PGRI 3 Malang, especially in Basic Electricity Installation Subject.